The Effectiveness of Mind Mapping Technique in Teaching Reading Comprehension of Narrative Text at The Second Grade Students’ of Sma Islam Al-Hikmah Mayong in the Academic Year of 2017/2018 - Arnita Dwi Septiyani (Universitas Islam Nahdlatul Ulama Jepara, 2017)
The objective of this study is to examine the effectiveness of mind mapping technique applied in teaching reading comprehension of narrative text. In this study, the data collected by using quantitative research through experimental research. The study was carried out in two classes; the experimental class and the controlled class. The data were collected through tests which were delivered into the pre-test and the post-test. The result of the study showed that using mind mapping technique is effective in teaching reading comprehension of narrative text The gained score of the experimental class (28.46) is higher than the controlled class (21.34). from the result of statistic calculation, it is obtained that the value of t-observation (to) is 2.39 and the degree of freedom (df) is 50. In the table of significance 5%, the value of degree of significance is 2.00. comparing those values, the result is 2.39 > 2.00 which means t-observation (to) score is higher than t-table (tt) score. In other word, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. Therefore, teaching reading comprehension of narrative text by using mind mapping technique is effective.